Literature Analysis: Local Community Involvement in Mangrove Forest Ecotourism Management in Indonesia - Amelia Retno Eka Putri; Asramid Yasin; Dinda Tri Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia has vast mangrove forest potential with high biodiversity and great ecological benefits. One of the developing management approaches is community-based mangrove ecotourism which not only emphasizes economic aspects but also environmental conservation. This study aims to analyze the involvement of local communities in mangrove ecotourism management and its impact on mangrove forest conservation in Indonesia. The method used is literature analysis with a descriptive-qualitative approach to ten studies published in the last 5-10 years. The results of the analysis show that active community participation in planning, implementing and evaluating the management of ecotourism areas contributes significantly to the sustainability of mangrove ecosystems. Despite the challenges of unequal capacity and strategic roles, this study confirms that community involvement is an important pillar in the success of community-based conservation. Thus, a collaborative approach between the community, government, and other stakeholders needs to be continuously strengthened to support ecotourism as well as mangrove conservation.